Ibn Arabi, Malami-Bayrami Dervish Order and the 17th Century Ottoman Balkans / İbn Arabî, Melamî-Bayrâmî Tarikatı ve 17 Yüzyılda Osmanlı Balkanları - Özkul, Ali Efdal; Ilić, Slobodan (Journal of History Culture and Art Research, 2017)
Abstract The controversy concerning the spiritual legacy of Muhy al-din ibn ‘Arabi (d. 1240) in the intellectual life of the Ottoman Empire reached its peak in the first decades of the 17th century. It is only natural that the most important protagonists in the related discourse were members of dervish orders whose teachings were more deeply influenced by the work of the magister magnus, Halwati and Bayrami in particular. The same years also witnessed an endeavour on the part of Malami-Bayrami order to be reconciled with the state authorities and the orthodox ulema, and to regain its prestige which had been seriously imperilled by a chain of trials and eventual persecution of its heterodox protagonists Isma’il Ma’shuqi (d. 1538), Husam al-din Anqarawi (d. 1557), and lastly Malami qutb Hamza Bali (d. 1573) and his Bosnian followers. Especially active were two Balkan murids of Hamza Bali’s successor Hasan Qabaduz (d. 1601): Husayn Lamakani (d. 1625), and ‘Abd Allah Bosnawi (d. 1644). The latter was the most fervent defender of Ibn ‘Arabi and apologist of wahdat al-wujud among his Ottoman contemporaries, and was generally known as commentator of Ibn ‘Arabi’s magnum opus Fusus al-Hikam. Öz Muhyuddîn ibn ‘Arabi’nin (ö. 1240) Osmanlı İmparatorluğu’nun entelektüel hayatında bıraktığı manevi mirası üzerine tartışmalar 17. yüzyılın ilk on yılında zirveye ulaşmıştır. İbn-i Arabi’nin öğretilerinde, Şeyh-i Ekber’in eserinin en fazla etki bıraktığı tarikatların (özellikle Halvetî ve Bayrâmî) üyelerinin, ilgili diyalogda en önde gelenler arasında olmaları gayet doğaldır. Söz konusu dönem Melamî-Bayramî tarikatının devlet otoritesi ve ulema ile barışma teşebbüsüne denk gelmekteydi. Adı geçen tarikatın itibar kazanmasında Hamza Bali’nin halifesi Hasan Kabaduz (ö. 1601)’un Balkan asıllı müritleri olan Hüseyin Lamekani (ö. 1625) ve Abdüllah Bosnevi (ö. 1644) önemi büyüktür. Ibn ‘Arabi’nin Osmanlı Devleti’ndeki çağdaşları arasında vahdet-i vücûdun en önemli savunuculardan sayılan Abdüllah Bosnevî, İbnü ‘l-Arebî’nin başyapıtı Fusûsu‘l-Hikem’ın şarihi olarak alelumum ün kazanmıştır.